Green Synthesis of Zinc Oxide Nanoparticles Using Clove Oil Extract (Syzygium aromaticum) and Evaluate their Antibacterial Activity against MRSA - Hashim, Mays U.; Ibrahim, Orooba M. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
There is a crucial need for the development of effective antimicrobial agents due to the rising incidence of hospital-acquired bacterial infections caused by multidrug-resistant microbes, leading to significant mortality and morbidity worldwide. Therefore, the current study aimed to synthesize zinc oxide nanoparticles (SaZnONPs) using clove extract through an environmentally friendly technique and to investigate their antibacterial activity against MRSA (Staphylococcus aureus). Clove extract acts as both a capping and reducing agent in the formation of ZnO-NPs. The formation of SaZnONPs was confirmed using various analytical techniques. Initially, clove extract was incubated with a zinc nitrate solution, and the subsequent change in color of the solution indicated the reduction of zinc nitrate ions to ZnO nanoparticles. UV-visible spectroscopy revealed a surface plasmon resonance band of SaZnONPs at 329.26 nm. Additionally, SEM imaging indicated that the nanoparticles had an average size of 41 nm and exhibited a spherical shape. The antibacterial activity of SaZnONPs was evaluated against MRSA using agar well diffusion and minimum inhibitory concentration assays. The phytochemicals present in clove extract facilitated the synthesis of stable ZnO-NPs, demonstrating promising antibacterial properties.